Concentration of Petroleum-Hydrocarbon Contamination Shapes Fungal Endophytic Community Structure in Plant Roots - Bourdel, Guillaume; Roy-Bolduc, Alice; St-Arnaud, Marc; Hijri, Mohamed (Frontiers in Microbiology, 2016)
Plant-root inhabiting fungi are a universal phenomenon found in all ecosystems where plants are able to grow, even in harsh environments. Interactions between fungi and plant roots can vary widely from mutualism to parasitism depending on many parameters. The role of fungal endophytes in phytoremediation of polluted sites, and characterization of the endophytic diversity and community assemblages in contaminated areas remain largely unexplored. In this study, we investigated the composition of endophytic fungal communities in the roots of two plant species growing spontaneously in petroleum-contaminated sedimentation basins of a former petro-chemical plant. The three adjacent basins showed a highly heterogeneous patterns of pollutant concentrations. We combined a culture-based isolation approach with the pyrosequencing of fungal ITS ribosomal DNA. We selected two species, Eleocharis erythropoda Steud. and Populus balsamifera L., and sampled three individuals of each species from each of three adjacent basins, each with a different concentration of petroleum hydrocarbons. We found that contamination level significantly shaped endophytic fungal diversity and community composition in E. erythropoda, with only 9.9% of these fungal Operational Taxonomic Units (OTUs) retrieved in all three basins. However, fungal community structure associated with P. balsamifera remained unaffected by the contamination level with 28.2% of fungal OTUs shared among all three basins. This could be explained by the smaller differences of pollutant concentrations in the soil around our set of P. balsamifera sampless compared to that around our set of E. erythropoda samples. Our culture-based approach allowed isolation of 11 and 30 fungal endophytic species from surface-sterilized roots of E. erythropoda and P. balsamifera, respectively. These isolates were ribotyped using ITS, and all were found in pyrosequensing datasets. Our results demonstrate that extreme levels of pollution reduce fungal diversity and shape community composition in E. erythropoda. Our findings shed light on the effect of soil petroleum contamination on fungal endophytic communities and could help to develop strategies for improving phytoremediation using fungal endophytes.